Nuclear heritage of the south of Spain. Diagnosis and proposals - Muñoz-Castillo, Juan Antonio; Olcina-Cantos, Jorge (Revista de Estudios Andaluces, 2022)
This paper is an update of the existing nuclear heritage in southern Spain. Old uranium mines, nuclear fuel factories, nuclear waste warehouses or places affected by nuclear accidents have a set of possibilities beyond their relation to uranium activity. The state of existing nuclear facilities in southern Spain, which form a heritage complex that deserves institutional attention and may have opportunities for its transformation into a resource for educational or tourist use, is analyzed and valued. From the detailed analysis of each element to the object of study, the diagram of strengths and weaknesses of the whole has been established. This suffers a certain stigmatization that should be reverted in a series of actions conducive in a sustainable way to comprehensiveness in their regional environments.